ACT-15 AD-SGE-REIC GENE THERAPY FOR MALIGNANT GLIOMA. (16th December 2019) - Kurozumi, Kazuhiko; Fujii, Kentarou; Shimazu, Yosuke; Tomita, Yusuke; Matsumoto, Yuji; Uneda, Atsuhito; Tsuboi, Nobushige; Kaneda, Keisuke; Makino, Keigo; Kumon, Hiromi; Date, Isao
Abstract: INTRODUCTION: Malignant gliomas are one of the most common and aggressive intracranial neoplasms in humans. Expression of the gene encoding reduced expression in immortalized cells/Dickkopf-3 (REIC/Dkk-3) is reduced in a variety of human cancer cells. We previously showed the antitumor effect of an adenoviral vector carrying REIC/Dkk-3 gene (Ad-CAG-REIC). Recently, we have also developed a novel adenoviral vector expressing REIC/Dkk-3 (Ad-SGE-REIC). We assessed the anti-glioma effect of the Ad-SGE-REIC and planned a clinical trial of Ad-SGE-REIC for malignant glioma. MATERIALS AND METHODS: We evaluated a cytotoxicity assay to treatments with Ad-SGE-REIC, Ad-CAG-REIC, or Ad-LacZ (control) using malignant glioma cells. The survival of mice in each group was analyzed by the Kaplan-Meier method. We also performed Good Laboratory Practice (GLP) toxicology tests and prepared a protocol for this clinical trial. RESULTS: The treatment with Ad-SGE-REIC showed the number of malignant glioma cells attached to the bottom of culture wells was significantly reduced in a time-dependent manner. Mice treated with Ad-SGE-REIC significantly prolonged survival time more than those treated with other vectors. A cGMP product of Ad-SGE-REIC was developed and supplied by a startup biotech company, Momotaro-Gene Inc. We conducted GLP toxicology tests using the intracranial injection of higher doses of Ad-SGE-REIC at Shin Nippon Biomedical Laboratories (SNBL Japan). After finishing the consultation with Pharmaceuticals and Medical Devices Agency (PMDA), we prepared a protocol for a phase I/IIa clinical trial of Ad-SGE-REIC for the treatment of recurrent malignant glioma with our academic research organization (ARO), supported by Japan Agency for Medical Research and Development (AMED). This protocol was reviewed by our institution review board in March 2019. We submitted a notification of this trial in April 2019. CONCLUSIONS: We demonstrated the anti-glioma effect of Ad-SGE-REIC. We start a phase I/IIa clinical trial of Ad-SGE-REIC for the treatment of recurrent malignant glioma (https://jrct.niph.go.jp/en-latest-detail/jRCT2063190013 ).